Penetapan Tersangka Sebagai Obyek Praperadilan - Ely Kusumastuti (Universitas Airlangga, 2018)
Background of this article is the legal uncertainty after the Constitutional Court (MKRI) verdict No. 2/PUU-XII / 2014 on April 28, 2015 which has added pre-trial object with the determination of suspects, foreclosures and searches. The legal issues of this article are the philosophical foundation of the pre-trial, ratio decidendi of pre-trial verdict related to the determination of suspects and ratio decidendi of Constitutional Court (MKRI) Verdict No. 21 / PUU-XII / 2014 on April 28, 2015. This discussion and analysis of this article are the statutory, conceptual, comparative and case approaches. The conclusions of this article are: First, the pretrial philosophical foundation is to provide human rights protection in the use of forceful efforts by investigators and prosecutors. Second, the ratio decidendi pretrial verdict on behalf of Budi Gunawan and the Verdict of Constitutional Court (MKRI) No. 21/PUU-XII/2014, April 28, 2015 which has decided determination of suspect as objects of pretrial, has shifted from philosophy of pretrial in the Criminal Code and not according to the principles of fairness, certainty and expediency. The authority of the Pretrial Institution in the Criminal Procedure Code only examines the procedural truth in this case the investigator’s and prosecutor’s actions, while to examine the material truth related to the suspect’s acts is the absolute authority of the case trial session.